Chapter 21 Succeeding at Learning Development - Hood, Sonia (Taylor & Francis, 2024)
This chapter focuses on how we, as Learning Developers, can be successful in our roles, have strategic influence and remain committed to our core values. It discusses strategies we can adopt to demonstrate our expertise and relevance to our academic colleagues including: speaking to their concerns; making the most of funding opportunities; preparing to contribute to School meetings; and volunteering to join university wide working groups. It also discusses how we can harness informal structures and network with other third space professionals to support our shared objectives and get our voices heard. It argues that we must own our expertise, see the value in our unique perspective and use this to influence strategy. Finally, it raises the importance of enhancing and promoting our own professional development, taking opportunities for training and development, and gaining qualifications and professional accreditation for the work that we do. Navigating this third space can be challenging but by being nimble, tailoring our approaches to the different audiences, evidencing our expertise and remaining committed to our core values, we have the opportunity to develop our role into one with influence and recognition.